Bivalvia Community Structure in The Poton Bako Beach Area, Jerowaru, East Lombok - Raudatul Jannah; Adam Restu (Jurnal Biologi Tropis, 2023)
The bivalvia class is a class within mollusca that includes all types of shellfish that have a pair of shells. The aim of this research is to determine the structure of the bivalve community in the coastal waters of Poton Bako, East Lombok. This research was conducted on the coast of Poton Bako, Jerowaru, East Lombok. This research uses a proportional sampling method with quadratic transects. This research variable includes type and bivalves. In this study, 275 individuals of bivalve species were found. The research results show that the ecological condition of Poton Bako is in the relatively good category because the level of Bivalvia diversity is moderate at 1.38 with a high evenness index of 0.60 and a low dominance index of 1.13. In this research, it is necessary to carry out further research regarding distribution patterns, exploitation rates, characteristics of pemadak, and conservation efforts.